bx-a=ac

Simple and best practice solution for bx-a=ac equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for bx-a=ac equation:


Simplifying
bx + -1a = ac

Reorder the terms:
-1a + bx = ac

Solving
-1a + bx = ac

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1ac' to each side of the equation.
-1a + -1ac + bx = ac + -1ac

Combine like terms: ac + -1ac = 0
-1a + -1ac + bx = 0

Add '-1bx' to each side of the equation.
-1a + -1ac + bx + -1bx = 0 + -1bx

Combine like terms: bx + -1bx = 0
-1a + -1ac + 0 = 0 + -1bx
-1a + -1ac = 0 + -1bx
Remove the zero:
-1a + -1ac = -1bx

Combine like terms: -1bx + bx = 0
-1a + -1ac + bx = 0

The solution to this equation could not be determined.

See similar equations:

| 10x=ex-28 | | v^4-13v^3+36v^2=0 | | 15*ln(1+.5x)=ln(2+15x) | | 2(2x+1)=3x-4(1-x) | | 6x+24=6x+12 | | y+y^2+1=14 | | -18(-4)= | | 1.3x-0.28=-2.1 | | 48n-9n^2=36 | | -13+y+y^2=0 | | 0=5x^4-2x^2-4 | | -400.00x+4000=0.00 | | -b+ax=cb | | 3a+5(a-4)= | | -4.5=-.5(x-7.1) | | 10x-23=-123 | | (v^2-13v-36)=0 | | -29+s=-58 | | v^2(v^2-13v-36)=0 | | 4-6p+5p= | | ax-b=cb | | 36=24N-3N^2 | | y=-30+5 | | 24N-3N^2=48N-9N^2 | | 22x^2+33x=0 | | 5(x-20)=5(x-4) | | 16+5p=51 | | -400x+4000=2000 | | -(2p-8)-6p=20+4(p+6) | | 3(h-6)=3(h+4) | | w(n)=4n+4 | | 6(2n+5)=54 |

Equations solver categories